SISTEM PENJERNIHAN AIR MASYARAKAT DI DESA MUARA GEMBONG KABUPATEN BEKASI - Ratu Amilia Avianti; Aam Amaningsih Jumhur; Agus Dudung; Gaguk Margono (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract All activities in the Muara Gembong Coastal Area develop in line with the development of the area^s population, which affects the coastal ecosystem, resulting in a decrease in the quality of the coastal ecosystem and environmental conditions. The current environmental conditions in the Muara Gembong Coastal Area are abrasion, flooding and sanitation. unfavorable environment. Based on the problems identified the environmental conditions in the Muara Gembong Coastal Area are in line with changes in the function of the coastal ecosystem to meet the lives of coastal communities. The people of Muara gembong village have water sources that are not fit for drinking, so they need water purification technology. So training to make water purification technology to get drinking water. Furthermore, it will improve health and the economy to create a prosperous society. Abstrak Seluruh kegiatan di Wilayah Pesisir Muara Gembong berkembang sejalan dengan perkembangan penduduk di wilayah tersebut, yang berdampak pada ekosistem pesisir sehingga mengakibatkan penurunan kualitas ekosistem pesisir dan kondisi lingkungan. Kondisi lingkungan saat ini di Wilayah Pesisir Muara Gembong adalah abrasi, banjir dan sanitasi. lingkungan yang tidak menguntungkan. Berdasarkan permasalahan yang diidentifikasi kondisi lingkungan di Kawasan Pesisir Muara Gembong sejalan dengan perubahan fungsi ekosistem pesisir untuk memenuhi kehidupan masyarakat pesisir. Masyarakat Desa Muara gembong memiliki sumber air yang tidak layak untuk diminum, sehingga membutuhkan teknologi penjernihan air. Maka pelatihan membuat teknologi penjernihan air untuk mendapatkan air minum. Selanjutnya akan meningkatkan kesehatan dan perekonomian untuk mewujudkan masyarakat yang sejahtera.